Pengaruh Evaluasi Proses Pembelajaran Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam Di SMA Muhajirin - Hilyatun Awaliya; Mustika Fitriani; Nanda Firmansyah (Turabian: Jurnal Pendidikan Islam, 2023)
This study aims to determine the effect of evaluation on the learning process on student learning outcomes in PAI subjects in class X (Ten) SMA Muhajirin Bekasi. Evaluation is very important in the world of education because evaluation is a process in which a value judgment or decision is made from various observations, backgrounds and training of the evaluator. With the evaluation in the learning process educators can find out students' understanding of the material that has been taught so that they have achieved the goals that have been set. This research is a quantitative study using descriptive statistical data analysis, which aims to find out how student learning outcomes are in PAI subjects in class X (ten) SMA Muhajirin Bekasi. The method used in this study is using correlation analysis, which aims to determine whether or not there is a relationship between variables so that it can make it easier to determine and predict the values of other variables. The population in this study totaled 37 students from all classes XA and XB, and the sample used in this study was class XA and XB SMA Muhajirin Bekasi, totaling 20 students from class XA and class XB, totaling 17 students. With a total of 37 samples. Sampling using random sampling technique, namely by taking random samples in class XA and XB. After being analyzed, it turns out that based on the SPSS calculation results, two sample T-tests get a coefficient value of 0.422, which means a coefficient value of 0.4 to <0.6 = in the category of having a relationship between variables that is quite large or strong enough. then there is a significant influence between the evaluation of the learning process with learning outcomes. So there is an influence of the evaluation of the learning process on the results of PAI learning at SMA Muhajirin Bekasi. Evaluating the learning process that has been implemented.